Cerebrospinal fluid pleocytosis in acute lymphoblastic leukemia without central nervous system relapse: a report of three cases - Öner, Ahmet Faik; Yetgin, Sevgi; Uçkan, Duygu (The Turkish Journal of Pediatrics, 1999)
Three patients with acute lymphoblastic leukemia (ALL) developed mononuclear cells in the cerebrospinal fluid (CSF) after a flu-like history during maintenance treatment. None of the patients showed evidence of central nervous system (CNS) involvement by either clinical or laboratory follow-up. Although the presence of > 5 mononuclear cells/µl in the CSF is important, it may not necessarily indicate CNS disease. Clinical findings, history and cell morphology must be evaluated before deciding on further treatment.
Keywords: acute lymphoblastic leukemia; central nervous system involvement; pleocytosis